2017
DOI: 10.1038/s41598-017-17442-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of peripheral blood derived human NK cells in a novel human IL-15- transgenic NOG mouse

Abstract: We generated a novel mouse strain expressing transgenic human interleukin-15 (IL-15) using the severe immunodeficient NOD/Shi-scid-IL-2Rγnull (NOG) mouse genetic background (NOG-IL-15 Tg). Human natural killer (NK) cells, purified from the peripheral blood (hu-PB-NK) of normal healthy donors, proliferated when transferred into NOG-IL-15 Tg mice. In addition, the cell number increased, and the hu-PB-NK cells persisted for 3 months without signs of xenogeneic graft versus host diseases (xGVHD). These in vivo-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 42 publications
3
58
0
1
Order By: Relevance
“…Our results also demonstrated that inhibition of teratomas formation was possible only if hiPSCs were injected prior to the adoptive transfer of total PBMCs or purified NK cells, consistent with the prior observation that hiPSCs-derived myoblasts are not the target of NK cells in vitro and in vivo (Benabdallah et al submitted). Moreover, in the absence of recombinant human IL-15 to support the proliferation of NK in our mice [14], our results also suggest that the relatively low number of NK cells injected during the adoptive transfer procedure was sufficient to prevent the growth of teratomas. These results suggest that if immunosuppressive drugs were to be used to increase engraftment of iPSC-derived cells, it would be very important to insure no inhibition of the NK cell compartment to lower the risk of forming a teratoma.…”
Section: Discussionmentioning
confidence: 86%
“…Our results also demonstrated that inhibition of teratomas formation was possible only if hiPSCs were injected prior to the adoptive transfer of total PBMCs or purified NK cells, consistent with the prior observation that hiPSCs-derived myoblasts are not the target of NK cells in vitro and in vivo (Benabdallah et al submitted). Moreover, in the absence of recombinant human IL-15 to support the proliferation of NK in our mice [14], our results also suggest that the relatively low number of NK cells injected during the adoptive transfer procedure was sufficient to prevent the growth of teratomas. These results suggest that if immunosuppressive drugs were to be used to increase engraftment of iPSC-derived cells, it would be very important to insure no inhibition of the NK cell compartment to lower the risk of forming a teratoma.…”
Section: Discussionmentioning
confidence: 86%
“…The severity of immunodeficiency has been increased by combining mutations in the aforementioned genes and/or Prkdc. 167 , 174 , 176 , 177 …”
Section: Ratsmentioning
confidence: 99%
“… 128 Additionally, Prkdc mutations to obtain a SCID phenotype in many mouse strains (like all NOD-derived immunodeficient strains such as NSG and NOG) increase toxicity due to irradiation in certain models, such as in cancer treatments, since PRKDC is an enzyme essential in DNA repair and its absence generates uncontrolled toxicity in the host tissues. Some 174 , 176 , 182 but not all 177 immunodeficient rats also carry a mutation in the Prkdc gene.…”
Section: Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice transgenic for human cytokine genes have improved development of cell lineages reliant on cytokines that are not cross-reactive between mice and humans. For example, mice transgenic for human GM-CSF, IL-3, and SCF support greater development of human myeloid lineages [16], whereas mice transgenic for human IL-2 [17] and IL-15 [18] support better NK cell development and survival. Functionality, as opposed to levels of reconstitution, has also been improved through transgenic expression of human leukocyte antigens (HLA) in graft recipient mouse strains.…”
Section: Generation Of His Micementioning
confidence: 99%